Association between high mobility group box 1 protein and juvenile idiopathic arthritis: a prospective longitudinal study - Dan Xu; Yu Zhang; Zhi-Yong Zhang; Xue-Mei Tang (BMC, 2021)
Abstract Objective To analyze the levels of high mobility group box 1 (HMGB1) protein on different courses of juvenile idiopathic arthritis (JIA). Methods In our prospective longitudinal study, children with JIA were included with their blood samples collected at the first visit, 1-month, 3-month, and 6-month follow-up, respectively. Samples were also collected from healthy controls and children with reactive arthritis at the first visit. Levels of HMGB1 were determined using enzyme-linked immunosorbent assays. Clinical disease characteristics and routine laboratory findings were analyzed as well. Results A total of 64 children were enrolled, of whom 31 (48.4%) were female. The median age at the first visit for participants with JIA was 9.25 years (range, 1.42-15.42) and the median duration of disease was 2.38 months (range, 1.53-49.31). Serum HMGB1 levels at the first visit were significantly elevated in children with systemic JIA compared with other groups, and so were in enthesitis-related arthritis versus healthy controls. Significant correlations were established at the first visit between HMGB1 levels and duration of disease, C-reactive protein, percentage of neutrophils, and ferritin. Data from all samples revealed that serum HMGB1 levels in JIA were significantly associated with erythrocyte sedimentation rates, C-reactive protein, percentage of neutrophils, and disease activity scores. Conclusions Serum HMGB1 may be associated with clinical disease activity of JIA and specifically increased at the first visit in children with systemic JIA, suggesting its function as a sensitive inflammatory marker. Further large-scale studies are warranted to explore its spectrum in JIA.